An Appendix Origin Burkitt's Lymphoma Spreading into Genital Tract - Mustafa Ulubay; Fahri Burçin Fıratlıgil; Uğur Keskin; Ulaş Fidan; Mehmet Gamsızkan; Müfit Cemal Yenen; Ali Ergün (Medical Network, 2016)
Burkitt's lymphoma (BL) occurs commonly in children and young adults, whereas bilateral ovarian involvement is extremely rare. We report a patient with unusual symptoms for BL, mimicking an ovarian neoplasm. Here, our aim was also to point out that BL can spread into the genital tract. A 60-year-old woman presented with the complaint of abdominal pain for a few months. Abdominal distension and sensibility were observed upon physical examination of the patient, but no common "B" symptoms associated with lymphoma were noted. Our imaging studies revealed bilateral adnexal masses suggesting an ovarian tumour with positive laboratory findings. We performed an exploratory laparotomy and a total hysterectomy, bilateral salpingo-oophorectomy and right hemicolectomy with appendectomy. The hemicolectomy process was needed to reduce the tumour burden and because of the risk of intestinal obstruction risk that could arise from the tumour mass in the ileocecal valve. Observation of a frozen specimen indicated BL, so the surgery was ended. Although BL involving the genital tract is a rare condition in patients who have pelvic masses, BL can be one of the diseases that should be considered for specific diagnosis.